2013
DOI: 10.1016/j.jbiomech.2013.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the in vivo volumetric wear measurement for total knee prostheses in model-based RSA

Abstract: Implant failure related to polyethylene wear remains an important issue in total knee arthroplasty. Polyethylene wear is usually assessed in vivo by measuring the remaining insert thickness on X-ray images of the knee. To reflect the amount of wear debris more accurately, a 3-dimensional overlap measurement has been suggested, which is based on implant component models which are matched on calibrated stereo X-ray images using model-based roentgen stereophotogrammatic analysis. The goal of this study was to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…RSA has a reported accuracy for linear wear measurements in the range of 0.1 to 0.2 mm [31,47]. Phantom studies have suggested volumetric measurements are likely to be over-or underestimates of wear volume such that volumetric measurements are not as reliable as linear measurements of TKA wear with RSA [41,44]. Wear measurements can be taken at a single time point or serially in a prospective manner.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…RSA has a reported accuracy for linear wear measurements in the range of 0.1 to 0.2 mm [31,47]. Phantom studies have suggested volumetric measurements are likely to be over-or underestimates of wear volume such that volumetric measurements are not as reliable as linear measurements of TKA wear with RSA [41,44]. Wear measurements can be taken at a single time point or serially in a prospective manner.…”
Section: Introductionmentioning
confidence: 99%
“…For modern, more wear-resistant TKAs, more advanced methodologies for measuring TKA wear have been developed as research tools utilizing radiostereometric analysis (RSA) and single-plane fluoroscopy [13,17,31,41,[44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, van IJsseldijk et al expanded their measurements to volumetric wear, recording measured wear at varying knee flexion angles and observing that large differences in wear were observed at these different angles, and at most, 56% of the true volume was measured, resulting in poor accuracy and precision . The observations and limitations presented by this study in volumetric wear measurement led to our method of recording wear at different arm positions and taking the unique sum of intersecting overlap voxels.…”
Section: Discussionmentioning
confidence: 96%
“…While volumetric wear measurements have been made using microcomputed tomography (Fig. 1), it remains to be seen if the resolution of clinical radiographs combined with implant manufacturing tolerances and the measurement uncertainties associated with contemporary wear analysis techniques will allow accurate volumetric wear assessments [12]. As a consequence, robust validation of volumetric wear accuracy would be essential since linear measurement uncertainties on the order of 0.1 to 0.2 mm could contribute to volumetric uncertainties of 10 to 20 cubic millimeters for each square centimeter of contact area.…”
mentioning
confidence: 99%